ETIKA KOMUNIKASI DALAM MANAGEMENT RELATIONSHIP (STUDI KUALITATIF : ETIKA KOMUNIKASI PETUGAS AFTAP TERHADAP DONOR DALAM MANAGEMENT RELATIONSHIP DI PMI KOTA SURAKARTA) - Desi Mayasari; Kristian Sanjaya (Jurnal Infokes, 2019)
Officers in providing services to prospective donors use communication ethics, for example be patient and always use good manners. Some donors cannot maintain their communication well due to the influence of the environment that is less conducive to the diverse conditions of the community.The purpose of this study is to describe and analyze the ethics of communication between Aftap Officers and donors at PMI Surakarta in establishing relationships.This type of research is a qualitative research with a case study approach. The subject of the research was the aftap officer at PMI Surakarta City. Withdrawal of informants through purposive sampling, with the type of key informant who then produces 1 key informant namely the head of the Medical Technical Section and 4 Aftap Officers.Data collection by in-depth interviews and observations. Analysis of the data, researchers perform data display, then perform data reduction and record.The results of the study are related to the ethical standards of communication between officers and donors in PMI Surakarta, namely the way an aftap officer serves donors by frequently greeting when entering the donor room, must not be indifferent, and of course must follow the rules, there are ways officers in giving when behaving with anyone that is still respecting fellow human beings without exception and the feelings felt by officers that are quite happy with donor responses because they can gradually give feedback positive messages conveyed about how to behave and communicate well, the purpose of which is to establish a positive relationship .